Expanding functions of lipoprotein receptors - Joachim Herz; Ying Chen; Irene Masiulis; Li Zhou (Journal of Lipid Research, 2009)
Lipoprotein receptors are evolutionarily ancient proteins that are expressed on the surface of many cell types. Beginning with the appearance of the first primitive multicellular organisms, several structurally and functionally distinct families of lipoprotein receptors evolved. Originally, these cell surface proteins were thought to merely mediate the traffic of lipids and nutrients between cells and, in some cases, by functioning as scavenger receptors, remove other kinds of macromolecules, such as proteases and protease inhibitors from the extracellular space and the cell surface. Over the last decade, this picture has fundamentally changed. We now appreciate that many of these receptors are not mere cargo transporters; they are deeply embedded in the machinery by which cells communicate with each other. By physically interacting and coevolving with fundamental signaling pathways, lipoprotein receptors have occupied essential and surprisingly diverse functions that are indispensable for integrating the complex web of cellular signal input during development and in differentiated tissues.